Digital Democracy and Youth Political Communication from the Perspective of Islamic Political Education - Nurmaliza Sembiring; Alya Mukhbita Wiyanti; Dinda Adhisty; Afsa; Arya Syahputra (Young Journal of Social Sciences and Humanities, 2026)
Digital technological advancements have brought significant transformations to political communication patterns among the youth. Social media has emerged as a sphere for political opinion formation, information dissemination, and an arena for ideological and interest conflicts. Utilizing a literature review method, this study aims to delineate political communication strategies within Islamic political education as an effort to build a more ethical and inclusive future for Indonesian democracy. The findings reveal that youth social media engagement is not yet fully accompanied by adequate political literacy and communication ethics. Consequently, Islamic political education needs to be operationalized through a humanistic and religious political communication approach, embedding values such as dialogue, tolerance, tabayyun (factchecking/verification), musyawarah (deliberation), and respect for diverse opinions. These strategies can be implemented through digital democracy literacy, dialogic learning, democracy simulations, and the strategic utilization of social media as a healthy space for political education.